O ensino religioso e sua influência na formação ética e social dos adolescentes - Costa, Hamutal Rocha da (2015)
Nowadays so much of the crisis of transmission of values is spoken in the society, especially reaching the adolescents and young in their existential dynamics concerning to their ethical and social formation. The present work seeks to understand what is happening with the individuals that compose the society and to know hat influences of religious education in ethic sand social education of adolescents in public schools in Boa Vista-RR. There search will be conducted with student volunteers, selected in a public school. A mixed questionnaire with closed and open and semi-structured interviews, conducted as a supplement to teachers and school management issues will be used. Also observation s in the context of school behavior and attitudes of the students during school religious teaching will take place. The methodology is an approach to qualitative nature and descriptive in nature, based on field research. Content analysis will guide the process of interpreting the answer to open questions. Closed question s are subjected to simple statistical analysis, which enable us to construct graphs. The data analyzed in the study will result in the construction of the Product: A Manual for Religious Education for the formation of ethical and social values.